Cobalt-based brazing filler metal for brazing of service damage area of high-temperature alloy hot end component with oxidation film on surface and preparation method of cobalt-based brazing filler metal

By adding high-active elements Ti and Zr to the cobalt-based brazing material, the problem of insufficient wetting and seam filling capacity when the oxide film on the surface of the high-temperature alloy is present, efficient brazing repair is achieved, repair costs are reduced, and the strength performance of the joint is improved.

CN119566617AActive Publication Date: 2025-03-07AVIC BEIJING INST OF AERONAUTICAL MATERIALS

Patent Information

Application Number
CN202411780004.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-07
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

When the existing cobalt-based solder is an oxide film on the surface of high-temperature alloy, the wetting and seam filling capacity are insufficient, resulting in defects such as unwelded joints on the brazed joints, and the cleaning of the oxide film is difficult and costly.

Method used

A cobalt-based active solder material is designed, containing Ti and Zr elements. Through its high activity, the liquid solder material can wet the base material in the presence of an oxide film on the surface of the high-temperature alloy, and promote wetting and filling of the solder material.

Benefits of technology

Good wetting and seaming on the surface of high-temperature alloys with oxide films is achieved, which reduces the need for oxide film removal, simplifies the repair process, significantly reduces the repair cost, and improves the strength performance of high-temperature alloy brazed joints.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119566617A_ABST
    Figure CN119566617A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of brazing, and relates to cobalt-based brazing filler metal for brazing a service damage area of a high-temperature alloy hot end component with an oxidation film on the surface. The brazing filler metal comprises, by weight, 17.0%-18.5% of Cr, 15.0%-16.5% of Ni, 8.0%-10.0% of W, 7.0%-9.0% of Ti, 1.0%-2.0% of B, 1.0%-2.0% of Zr, 0.4%-0.5% of C and the balance Co, and the brazing filler metal can be prepared into powder to be used. According to the brazing filler metal, the proper content of active elements Ti and Zr are added, so that the brazing filler metal has good activity, meanwhile, the oxidation resistance of a brazing filler metal matrix is not obviously reduced, the brazing filler metal can react with various oxides in the brazing process, wetting and joint filling are achieved, the brazing filler metal can be directly used for brazing repair of a service damage area of a high-temperature alloy hot end component with an oxidation film on the surface, and the service life of the high-temperature alloy hot end component is prolonged. And the surface treatment requirement of a service damage area is effectively lowered, the adaptability of a brazing repair process is improved, and the repair cost is greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of brazing, and relates to a cobalt-based active brazing filler metal for brazing and repairing a service damaged area of ​​a high-temperature alloy hot end component with an oxide film on the surface, and a preparation method thereof. Background Art

[0002] Cobalt-based brazing filler metals have better high-temperature performance than nickel-based brazing filler metals and can be used for brazing connections of high-temperature components. Table 1 shows the composition of cobalt-based brazing filler metals specified in navigation marks (cobalt-based brazing filler metal specifications, HB 20453-2018). These brazing fillers are suitable for high-performance brazing connections of various high-temperature alloys and other materials. They are currently widely used in aviation, aerospace and other fields. From the characteristics of these brazing fillers, these cobalt-based brazing fillers are rich in Co-Cr-Ni-W, but the composition and content of melting-reducing elements are different. The room temperature tensile strength of the K465 alloy brazed with B-Co45NiCrWB brazing filler metal reaches 85% of the parent material, and the high-temperature endurance performance reaches 50% of the parent material (Structure and properties of K465 high-temperature alloy joints brazed with different brazing fillers. Mao Wei, Zhou Yuan, Ye Lei, etc. Spot Welding Machine, vol.38No.9, 2008). The tensile strength of the DD5 single crystal alloy joint brazed with Co-Cr(18-20)-Ni(15-17)-W(4-5)-Si(7-9)-B(2-3)(wt%) brazing filler metal reaches more than 80% of the parent material (Analysis of microstructure and mechanical properties of DD5 single crystal high temperature alloy brazed joint. Sun Yuan, Hou Xingyu, Jin Tao, etc. Journal of Welding, vol.38No.1, 2017). From the application of cobalt-based brazing filler metal, high-performance horizontal joints can be obtained, but according to the composition characteristics of these brazing filler metals, the cleanliness of the surface of the high temperature alloy to be welded is very high. Once the cleanliness of the welded surface is not enough, the wettability and filling ability of the brazing filler metal will be affected, which will eventually lead to defects such as unwelded joints in the brazed joints.

[0003] Table 1 Cobalt-based solder composition specified in navigation marks

[0004]

[0005]

[0006] For the cracks, ablation and other damages caused by the cast high-temperature alloy blades and other engine hot end parts after service (such as Figure 1 As shown in the figure, brazing is required for repair. Currently, the main repairable brazing materials are the cobalt-based brazing materials listed in Table 1. These brazing materials cannot react with the oxide film, and the oxide film will prevent the brazing material from wetting the surface of the high-temperature alloy to be welded. Therefore, the oxide film needs to be thoroughly removed before brazing repair, otherwise it will affect the filling of the brazing material. The cleaning of the oxide film is extremely difficult and the cleaning cost is high.

[0007] Based on the above problems, in order to realize the brazing repair of the service damaged area of ​​the hot end component of the high-temperature alloy with the oxide film on the surface or the surface oxide film that cannot be completely removed, it is urgent to improve the wettability of the brazing material on the surface of the high-temperature alloy with the oxide film. Therefore, the present invention designs a new component brazing material, which will be widely used in the field of service damage repair of the hot end component of the high-temperature alloy. Summary of the invention

[0008] The purpose of the present invention is to provide a cobalt-based active brazing filler metal for brazing and repairing the service damaged area of ​​a high-temperature alloy hot end component with an oxide film on the surface and a preparation method thereof. By utilizing the high activity of Ti and Zr elements in the brazing filler metal, even when an oxide film exists on the surface of the service damaged area of ​​the high-temperature alloy hot end component, the liquid brazing filler metal can wet the base material, promote the wetting and filling of the brazing filler metal, and ensure the formation of the brazing seam.

[0009] To solve this technical problem, the technical solution of the present invention is:

[0010] On the one hand, a cobalt-based active brazing filler metal is provided for brazing and repairing service damaged areas of hot end components of high-temperature alloys with oxide films on their surfaces, characterized in that the composition and mass percentage of the brazing filler metal are (wt%): Cr 17.0-18.5, Ni 15.0-16.5, W 8.0-10.0, Ti 7.0-9.0, B 1.0-2.0, Zr 1.0-2.0, C 0.4-0.5, and Co balance.

[0011] The cobalt-based active solder strengthening elements and their corresponding mass percentages are: Cr 17.5-17.8, Ni 15.5, W 8.5-8.8, preferably Cr 17.5, Ni 15.5, W 8.8.

[0012] The active element composition and mass percentage of the cobalt-based active solder are: Ti 8.0-8.8, Zr 1.5-1.8, preferably Ti 8.0, Zr 1.5.

[0013] The composition and mass percentage of the melting point-reducing elements of the cobalt-based active solder are: B 1.2-1.4, C 0.46-0.48, preferably B 1.4, C 0.46.

[0014] On the other hand, a method for preparing a cobalt-based active brazing filler metal for brazing and repairing a service damaged area of ​​a high-temperature alloy hot end component with an oxide film on the surface is provided. The preparation method is as follows:

[0015] Step 1: prepare the ingredients according to the composition of cobalt-based solder; Step 2: smelt the solder alloy ingot, and repeatedly smelt it for no less than 3 times; Step 3: prepare the solder alloy ingot into powder, and then sieve it; Step 4: mix acetone and neutral gum to form a solution, and then mix it with the solder powder to prepare a solder paste.

[0016] In the step 1, Co, W, Ti and Zr are simple substances, B is Ni-B master alloy, C is Cr-C master alloy, Ni is simple substance and Ni-B master alloy, Cr is simple substance and Cr-C master alloy, and the proportions are made according to the designed components.

[0017] In the step 2, the mixed raw materials are placed in a crucible and smelted by induction melting or arc melting to prepare a solder alloy ingot.

[0018] In the step three, the solder alloy ingot is prepared into powder by argon atomization method, or the solder alloy ingot is prepared into foil by vacuum argon filling rapid quenching equipment, and then mechanically crushed to obtain powder.

[0019] In the step 4, acetone is mixed with neutral gum at a volume ratio of 45-55:1 to prepare a solution, and after precipitation and filtration, the solution is mixed with solder powder at a volume ratio of 1.5:1 to prepare solder paste, which is placed in a syringe and added to the soldering area of ​​the part when used.

[0020] By adopting the brazing filler metal of the present invention, high temperature alloys with oxide films such as Ti-O, Al-O, Cr-O, etc. on the surface to be brazed can be brazed at 1180-1220°C and heat preservation for 5-60 minutes.

[0021] The beneficial effects of the present invention are:

[0022] (1) In order to achieve good wetting and gap filling of the brazing filler metal in the service damaged area of ​​the hot end component of the high-temperature alloy with an oxide film, active elements must be added to the brazing filler metal matrix. The active elements are usually selected from Ti, Zr, Hf, etc. These active elements have a strong binding force with the Ni element, but a relatively weak binding force with Co. Therefore, in the present invention, the brazing filler metal is designed to use Co as the matrix, the Ni content is relatively low, and 7.0-9.0 (wt%) Ti and 1.0-2.0 (wt%) Zr are added. The brazing filler metal can show good activity, achieve wetting of the surface of the high-temperature alloy with an oxide film, and obtain a high-temperature alloy brazing joint with a high performance level.

[0023] (2) At present, there are two main methods for removing oxide films on the surfaces of hot-end components such as high-temperature alloy blades with high Al and Ti contents that are damaged by cracks, ablation, etc. after service: one is to completely remove the damaged area by using an electric spark method. This method is suitable for small-sized damage defects with good accessibility, but not for large-sized damage defects with poor accessibility; the other is to remove the oxide film by using a fluorine ion cleaning method. This method is not restricted in the location of the oxide film on the surface and is widely applicable, but the domestic fluorine ion cleaning equipment does not have mature manufacturing capabilities, equipment resources are scarce, and the cost of use is high. In order to meet the needs of repairing all damaged parts of hot-end components of high-temperature alloys and reduce the cost of oxide film removal, the present invention directly provides a high-temperature active brazing material, which bypasses the oxide film removal process of the damaged area in service and directly repairs the damage. The process is simple and the repair cost is greatly reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions implemented in the present invention, the following is a brief explanation of the drawings required to be used in the examples of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0025] Figure 1 This is a crack diagram near the exhaust slot on the trailing edge of a guide blade;

[0026] Figure 2 This is a crack diagram of a guide blade edge plate. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0028] The features of various aspects of the embodiments of the present invention will be described in detail below. In the detailed description below, many specific details are proposed to fully understand the present invention. However, it is obvious to those skilled in the art that the present invention can also be implemented without these specific details. The following description of the embodiments is only for a better understanding of the present invention by illustrating examples of the present invention. The present invention is not limited to any specific settings and methods provided below, but covers all product structures, any improvements, replacements, etc. of methods covered without departing from the spirit of the present invention.

[0029] In the various drawings and the following description, well-known structures and techniques are not shown to avoid unnecessarily obscuring the present invention.

[0030] The present invention discloses a cobalt-based active brazing filler metal for brazing and repairing a service damaged area of ​​a high-temperature alloy hot end component with an oxide film on the surface. The typical composition is shown in Table 1.

[0031] Table 1

[0032]

[0033]

[0034] Embodiment 1:

[0035] Step 1: Design the solder composition (wt%): Cr 17.5, Ni 15.5, W 8.8, Ti 8.0, B 1.4, Zr1.5, C 0.46, Co balance;

[0036] Step 2: weigh the metal or master alloy according to the designed composition and then mix;

[0037] Step 3: Melt the mixture by vacuum induction melting method, and repeat the melting for no less than 3 times;

[0038] Step 4: Prepare solder powder by argon atomization method, sieve the solder powder through a 100-mesh sieve, and select the sieve-undersized material;

[0039] Step 5: Acetone is mixed with neutral gum at a volume ratio of 50:1 to prepare a solution. After precipitation and filtration, the solution is mixed with solder powder at a volume ratio of 1.5:1 to prepare solder paste, which is then added to the brazing area of ​​the K465 plate sample with a clean surface and oxidized. The K465 surface oxide film is mainly composed of a mixture of Ti-O, Al-O, and Cr-O, and has a thickness of about 20 μm.

[0040] Step 6: Place the assembled sample in a vacuum furnace, raise the temperature to 1200°C at a rate of 8°C per minute, keep the temperature for 30 minutes, and then cool it in the furnace;

[0041] Step 7: After the samples were machined, they were subjected to a room temperature tensile strength test. The average tensile strength of the clean surface samples was 684 MPa, and the average tensile strength of the surface oxidized samples was 669 MPa. The strength levels of the two joints were comparable.

[0042] Embodiment 2:

[0043] Step 1: Design the solder composition (wt%): Cr 17.8, Ni 15.0, W 8.5, Ti 7.9, B 1.8, Zr1.6, C 0.46, Co balance;

[0044] Step 2: weigh the metal or master alloy according to the designed composition and then mix;

[0045] Step 3: Melt the mixture by vacuum induction melting method, and repeat the melting for no less than 3 times;

[0046] Step 4: Prepare solder powder by argon atomization method, sieve the solder powder through a 100-mesh sieve, and select the sieve-undersized material;

[0047] Step 5: Acetone is mixed with neutral gum at a volume ratio of 50:1 to prepare a solution, and after precipitation and filtration, it is mixed with solder powder to prepare solder paste, which is added to the brazing area of ​​the GH3536 high-temperature alloy plate sample with a clean surface and oxidation treatment. The surface oxide film of GH3536 is mainly composed of a mixture of Cr-O and Ni-O, and the thickness is about 25 μm;

[0048] Step 6: Place the assembled sample in a vacuum furnace, heat it to 1210°C at a rate of 10°C per minute, keep it warm for 20 minutes, and then cool it down in the furnace;

[0049] Step 7: After the samples were machined, they were subjected to a room temperature tensile strength test. The average tensile strength of the clean surface samples was 435 MPa, and the average tensile strength of the surface oxidized samples was 422 MPa. The strength levels of the two joints were comparable.

[0050] Embodiment three:

[0051] Step 1: Design the solder composition (wt%): Cr 18.2, Ni 16.2, W 9.8, Ti 9.0, B 1.6, Zr2.0, C 0.50, Co balance;

[0052] Step 2: weigh the metal or master alloy according to the designed composition and then mix;

[0053] Step 3: Melt the mixture by vacuum induction melting method, and repeat the melting for no less than 3 times;

[0054] Step 4: Prepare solder powder by argon atomization method, sieve the solder powder through a 100-mesh sieve, and select the sieve-undersized material;

[0055] Step 5: Acetone is mixed with neutral gum at a volume ratio of 50:1 to prepare a solution, and after precipitation and filtration, it is mixed with solder powder to prepare solder paste, which is added to the brazing area of ​​the K465 plate sample with a clean surface and oxidized. The K465 surface oxide film is mainly composed of a mixture of Ti-O, Al-O, and Cr-O, and has a thickness of about 20 μm.

[0056] Step 6: Place the assembled sample in a vacuum furnace, raise the temperature to 1180°C at a rate of 9°C per minute, keep the temperature for 60 minutes, and then cool it in the furnace;

[0057] Step 7: After the samples were machined, they were subjected to a room temperature tensile strength test. The average tensile strength of the clean surface samples was 665 MPa, and the average tensile strength of the surface oxidized samples was 647 MPa. The strength levels of the two joints were comparable.

[0058] Embodiment 4:

[0059] Step 1: Design the solder composition (wt%): Cr 17.3, Ni 15.0, W 9.5, Ti 8.5, B 1.5, Zr1.5, C 0.42, Co balance;

[0060] Step 2: weigh the metal or master alloy according to the designed composition and then mix;

[0061] Step 3: Melt the mixture by vacuum induction melting method, and repeat the melting for no less than 3 times;

[0062] Step 4: Prepare solder powder by argon atomization method, sieve the solder powder through a 100-mesh sieve, and select the sieve-undersized material;

[0063] Step 5: Acetone is mixed with neutral gum at a volume ratio of 50:1 to prepare a solution, and after precipitation and filtration, it is mixed with solder powder to prepare solder paste, which is added to the brazing area of ​​the K465 plate sample with a clean surface and oxidized. The K465 surface oxide film is mainly composed of a mixture of Ti-O, Al-O, and Cr-O, and has a thickness of about 20 μm.

[0064] Step 6: Place the assembled sample in a vacuum furnace, heat it to 1220°C at a rate of 10°C per minute, keep it warm for 40 minutes, and then cool it in the furnace;

[0065] Step 7: After the samples were machined, they were subjected to a room temperature tensile strength test. The average tensile strength of the clean surface samples was 462 MPa, and the average tensile strength of the surface oxidized samples was 454 MPa. The strength levels of the two joints were comparable.

[0066] Compared with the prior art, after the oxide film is removed and repaired by the brazing filler metal of the present invention, the tensile strength of the repaired sample can be comparable to the tensile strength of the surface clean sample. Among them, in each embodiment, the tensile strength of the surface clean sample reached 97.8%, 97%, 97.3%, and 98.3%, respectively. Compared with 85% and 80% in the prior art (background technology), the strength performance is greatly improved. The brazing filler metal of the present invention can show good activity, realize wetting of the surface of the high-temperature alloy with oxide film, and obtain high-performance high-temperature alloy brazing joints, which has significant technical effects.

[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the field can easily think of various equivalent modifications or substitutions within the technical scope disclosed by the present invention, and these modifications or substitutions should all be covered within the protection scope of the present invention.

Claims

1. A cobalt-based brazing filler metal for brazing the service damaged area of ​​a high-temperature alloy hot end component with an oxide film on the surface, characterized in that: The composition and mass percentage of the solder are (wt%): Cr 17.0-18.5, Ni 15.0-16.5, W 8.0-10.0, Ti 7.0-9.0, B 1.0-2.0, Zr 1.0-2.0, C 0.4-0.5, and Co balance.

2. As described in claim 1, the strengthening elements of the cobalt-based active solder and the corresponding mass percentages are: Cr 17.5-17.8, Ni 15.5, W 8.5-8.8, preferably Cr 17.5, Ni 15.5, W 8.

8.

3. As described in claim 1, the active element composition and mass percentage of the cobalt-based active solder are: Ti 8.0-8.8, Zr 1.5-1.8, preferably Ti 8.0, Zr 1.

5.

4. As described in claim 1, the composition and mass percentage of the melting point reducing elements of the cobalt-based active solder are: B1.2-1.4, C 0.46-0.48, preferably B1.4, C 0.

46.

5. A method for preparing the solder according to claim 1, characterized in that: The preparation method is as follows: Step 1: prepare the ingredients according to the composition of cobalt-based solder; Step 2: smelt the solder alloy ingot, and repeatedly smelt it for no less than 3 times; Step 3: prepare the solder alloy ingot into powder, and then sieve it; Step 4: mix acetone and neutral gum to form a solution, and then mix it with the solder powder to prepare a solder paste.

6. The preparation method according to claim 5, characterized in that: In the step 1, Co, W, Ti and Zr are simple substances, B is Ni-B master alloy, C is Cr-C master alloy, Ni is simple substance and Ni-B master alloy, Cr is simple substance and Cr-C master alloy, and the proportions are made according to the designed components.

7. The preparation method according to claim 5, characterized in that: In the step 2, the mixed raw materials are placed in a crucible and smelted by induction melting or arc melting to prepare a solder alloy ingot.

8. The preparation method according to claim 5, characterized in that: In the step three, the solder alloy ingot is prepared into powder by argon atomization method, or the solder alloy ingot is prepared into foil by vacuum argon filling rapid quenching equipment, and then mechanically crushed to obtain powder.

9. The preparation method according to claim 5, characterized in that: In the step 4, acetone is mixed with neutral gum at a volume ratio of 45-55:1 to prepare a solution, and after precipitation and filtration, the solution is mixed with solder powder at a volume ratio of 1.5:1 to prepare solder paste, which is placed in a syringe and added to the soldering area of ​​the part when used.

10. The preparation method according to claim 5, characterized in that: By adopting the solder of the composition of the present invention, high-temperature alloys with oxide films such as Ti-O, Al-O, Cr-O, etc. on the surface to be brazed can be brazed at 1180-1220°C and heat preservation for 5-60 minutes.

Citation Information

Patent Citations

  • Braze alloy composition with enhanced oxidation resistance and methods of using the same

    CN101363090A

  • High-temperature soldering solder for soldering inert anode for aluminium electrolysis and metal conductive rod

    CN102581517A

  • High-temperature Ti-Zr-based brazing filler dedicated to TiAl-based alloy as well as preparation method and brazing process of high-temperature Ti-Zr-based brazing filler

    CN106925906A

  • Brazing material for SiC ceramic brazing and brazing method

    CN109877413A

  • Cobalt-based powder brazing filler metal for high-temperature alloy connecting as well as preparation method and application of cobalt-based powder brazing filler metal

    CN109909641A

Cited By

  • Cobalt-based high-temperature alloy brazing filler metal and preparation method and welding method thereof

    CN120680187A